Social Panorama of Latin America 1999-2000 - United Nations (United Nations, 2001)
What are the objective reasons why so many Latin Americans do not feel safe and see themselves as being defenceless? Does the Occupational stratification engendered by current patterns of development promote social mobility and the growth of the middle class? In an effort to answer these questions, this publication examines the deterioration of conditions in the labour market. It also looks at the available means of accessing social services, with emphasis on the types of public policies needed to tackle the problems of social vulnerability and poverty. It presents analysis of occupational stratification, indicates what percentages of the labour force fall into high-, middle- and low-income groups and explores how these phenomena are related to educational and household income levels. It also discusses how the level and coverage of pension systems affect income distribution in Latin America.